Comparative Analysis on Essential Nutrient Compositions of 23 Wild Hazelnuts (Corylus heterophylla) Grown in Northeast China - Liying Fan; Jun Ren; Yuting Yang; Limin Zhang (Journal of Food Quality)
The essential nutrients of 23 wild hazelnuts (Corylus heterophylla) grown in northeast China were analyzed in order to sieve good species and study the factors effected on nut quality. Hazelnut kernels contained 45.76–62.78% fat similar to Corylus avellana and main fatty acids were oleic acid (79.75%), linoleic acid (15.42%), palmitic acid (3.29%), and polyunsaturated fatty acids ranged between 10.37% and 25.88%. Average protein, soluble sugar, starch, and ash contents of hazelnut kernels were 25.12%, 4.98%, 2.03%, and 3.04%, respectively. The amount of amino acids, mostly as glutamic acid, arginine, and aspartic acid, was also determined by the hazelnut varieties. The abovementioned variation was explained by growing environmental differences. Among them, the 11th sample was highest in protein content (30.21%) and 18th sample highest in fat content, while the 5th and 14th samples had relatively balanced nutrients. So, when planning to select new cultivars, we primarily considered different hazelnut qualities.